Kreativitas Guru Dan Orang Tua Dalam Meningkatkan Minat Belajar Anak Melalui Pendidikan Agama Kristen - Julmiati Samoiri; Sandra Rosiana Tapilaha (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Christian religious education is an important aspect in the formation of character and the development of children. In this context, teacher creativity and the role of parents play a significant role in increasing children's interest in learning through Christian religious education. However, there are challenges in terms of a lack of understanding of the importance of creativity, a lack of creative teaching methods, and suboptimal involvement between teachers and parents. Therefore, this study aims to analyze the role of teacher and parent creativity in increasing children's interest in learning through Christian religious education. Through a qualitative approach and data analysis, this study identified existing problems and provided workable solutions. The results of the study show that a deep understanding of the importance of creativity, the use of creative teaching methods, and the active involvement of teachers and parents can encourage children's interest in learning in the context of Christian religious education. This study provides practical recommendations to enhance the role of teacher and parent creativity in strengthening children's interest in learning through Christian religious education, with the hope of improving the quality of Christian religious education that children receive.